Exploring the Application of Sharia Contracts on Islamic Fintech Peer-to-Peer Lending in Indonesia - Fithria, Annisa (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
This study aims to explore the application of sharia contracts used by Islamic fintech peer-to-peer (P2P) lending in Indonesia. This study uses a literature study and content analysis by observing firms’ websites, providing the Islamic fintech P2P lending in Indonesia. Eight firms registered with OJK per October 2021 that disclose information regarding the application of sharia contracts are analysed. This study finds that all sharia fintech P2P lending in Indonesia applies sharia con-tracts according to Fatwa of DSN-MUI No. 117/DSN-MUI/II/2018, including al-bai’ (murabahah), ijarah, mudharabah, musharakah, wakalah bil ujrah, and qardh contracts. By exploring the application of sharia con-tracts on Islamic fintech P2P lending, this study fills a gap in the literature about Islamic fintech and provides an insight into the implementation of sharia contracts in Islamic fintech P2P lending in Indonesia. To the best of the author’s knowledge, this is one of the first studies to provide the explanation regarding the application of sharia contracts in Islamic fintech P2P lending in Indo-nesia. The finding reveals that the implementation of sharia contracts on sharia fintech P2P lending regis-tered with OJK are in accordance with Fatwa of DSN-MUI.